The Role of MADA to Improve Paddy Sub-Sector in Kedah Darul Aman - Dian Rahmita Sari (2013)
Agricultural still plays an important role and gives contributions through its projects or programs to the development of Malaysia; self-sufficiency level has been focused on paddy and rice production with the granary areas as the concentrated area for paddy production areas. Kedah, which known as the “Rice Bowl of Malaysia”, is one of the states in Malaysia with the biggest granary areas, and it is under the management of Muda Agriculture Development Authority (MADA). Even thought MADA contributes about 38.90% to the total national rice production but MADA still faces the low productivity issue. This study conducted to explore the programs/projects that have been planned and implemented by MADA and the government to overcome the issue. Moreover this study also wanted to analyse the impact of the programs, projects and policies to increase total paddy production and improve the paddy sub-sector in Muda Area, Kedah. This study used descriptive analysis with observation, seminar, and interview with MADA and UPEN representatives as the source of primary data. Data checking of the official document, related articles and journals are used as the secondary data. There are five programs/projects that have been planned and implemented by MADA in order to overcome the productivity issue and with good management of paddy farms under MADA it will continually improve. The impact of the programs and policies by MADA and the government show a positive impact, each of the programs and policies contribute to the increase of total production and the average gross yields the paddy production in Muda Area, Kedah.